Lessons learned from the 2013 Calgary flood: Assessing risk of drinking water well contamination. (March 2017) - Eccles, Kristin M.; Checkley, Sylvia; Sjogren, Darren; Barkema, Herman W.; Bertazzon, Stefania
Abstract: A devastating flood occurred in southern Alberta on June 19, 2013, from greater than normal snowfalls in the Rocky Mountains and excess precipitation during the early spring that left soils saturated and unable to absorb any additional precipitation. This flood was Canada's most costly natural disaster, with five to six billion Canadian dollars in damages. The first objective of this study was to determine if the flood caused an increase in private drinking water well contamination in the Calgary Health Zone by comparing contamination rates to previous years. The second objective was to determine which environmental factors were associated with contamination during this flood event. Test results of total coliforms (TC) and Escherichia coli (EC) of private water wells were used to determine contamination. A geographically weighted Poisson regression analysis suggested that TC contamination was not associated with this flood. The EC contamination is positively associated with floodways, flood fringe, farms, and negatively associated with intermittent water (sloughs). These results suggest that for the 2013 flood, individual well characteristics are more important than surrounding geographic features. Thus, it is recommended that homeowners who live in a high-risk area ensure their wells are properly maintained to reduce risk of water well contamination. Highlights: A devastating flood occurred in southern Alberta in June of 2013. A higher proportion of private drinking water wells were contaminated in 2013 when compared with previous years. A small amount of the variance in water well contamination with EC was significantly explained by environmental factors. Individual well characteristics, such as well maintenance, may be better predictors of water well contamination. Homeowners living in a high-risk area should ensure their wells are properly maintained to reduce risk of water well contamination.